Determinan ekspor crumb rubber di Indonesia - Agus Pranoto, Eko; Hodijah, Siti; Nurjanah, Rahma (e-Journal Perdagangan Industri dan Moneter, 2018)
This study aims to determine the development and influence of exchange rate, inflation, area, and production on crumb rubber exports in Indonesia for the period 1995 – 2017. The type of research used to analyze the data in this study is descriptive quantitative. This study uses multiple linear regression analysis based on Ordinary Least Square (OLS). Based on the results of the regression calculation of the development of each variable, namely exchange rate, inflation, area, and production, it is obtained by these four variables that growth has fluctuated throughout the research period which can be caused by economic conditions or can be caused by the influence between variables. Keyword : Export value, Exchange rates, inflation, wide of land and production in Indonesia